Educator Knowledge and Implementation of Assistive Technology to Support Challenging Behaviors: An Exploratory Inquiry. Issue 3 (September 2021) - Emerling, Christopher R.; Wilkinson, Sarah; Maggin, Daniel M.
Emerging trends and advancements in technology allow educators to develop dynamic learning environments to support their students' academic and behavioral needs. The study documented the lived experience of special educators using assistive technology (AT) to support behavioral challenges in students with disabilities and the environmental factors that support educator's use of AT. Fifteen educators who worked in K–12 schools participated in semi-structured interviews and completed a researcher-developed Assistive Technology Treatment Integrity Checklist (ATTIC). This exploratory study indicated that participants had limited experiences using AT to target challenging behaviors. However, participants used technology to support evidence-based interventions or customized instructional technologies to manage students' needs. Our findings also indicated that school structures impacted AT-related attitudes and eventual use. The findings from this study add to the literature on technology supports for students with challenging behaviors. Implications for practice and future research are also discussed.